(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2017)
There are more and more modern logistics systems on the market that, as part of control systems, must guarantee production flexibility, required delivery dates, market readiness and liability for binding capital into inventory. Market globalization imposes the necessity of meeting certain standards in business that guarantee the quality of work done. The rapid development and use of information and communication technologies in support of the individual needs of users are becoming increasingly important for successful implementation of business activities. The paper analyzes the role of information and communication technologies in logistic processes and in the integration of logistics systems. Examples from practice confirm the reasons for increased investments made by companies engaged in this segment of work with an aim to optimize business operations and increase profits. The emphasis is placed on the significant role of information technology in logistics operations, current results and applications, as well as possible future applications. Keywords: Information technology, management, logistics systems, logistics processes, optimization